Electromechanically induced membrane restructuring enables learning and memory - Peter T. Podar; Dima Bolmatov; Teshani Kumarage; Rana Ashkar; Ariana Adkisson; Olivia Ziemer; Victoria Sullivan; Ahmed S. Mohamed; Joseph. S. Najem; C. Patrick Collier; John Katsaras (Proceedings of the National Academy of Sciences, 2025)
Human neural networks of interconnected neurons have evolved to be remarkably efficient and are capable of learning and memory through the brain’s synaptic plasticity, including short-term plasticity (STP), and long-term potentiation (LTP) and depression (LTD). These activity-dependent mechanisms induce changes in synaptic efficiency over both transient and extended timescales. Understanding the molecular basis of learning and memory is central to deciphering brain function and advancing therapeutics for neurodegenerative diseases. Here, we report that lipid bilayers with embedded gramicidin A ion channels can structurally reorganize when interrogated using a neurologically inspired electrical stimulation protocol, adopting metastable structures with enhanced STP response and emergent LTP or LTD. Specifically, voltage-induced electrocompression is found to restructure membranes, driving them into nonequilibrium steady states with enhanced stability and increased ionic conductivity, leading to stronger and persistent membrane ion conductance. These results show how membrane restructuring and emergent complexity may regulate synaptic plasticity at the molecular level.